1996
DOI: 10.1161/01.res.79.4.857
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Increase in Aortic Endothelial Nitric Oxide Synthase Expression In Vivo in a Model of Chronic High Blood Flow

Abstract: Physiological adaptation of normal blood vessels to acute or chronic changes in blood flow is endothelium dependent. In vitro studies have shown that, among other genes, NO synthase (NOS) 3 mRNA and protein expression is enhanced by acute elevation of shear stress in endothelial cells. We have investigated the effect of chronic high blood flow on NOS3 mRNA and protein expression in rat aorta. NOS3 mRNA levels were measured by quantitative polymerase chain reaction (PCR) in the aortas of 12 rats with arterioven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
142
0
2

Year Published

1997
1997
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(153 citation statements)
references
References 28 publications
9
142
0
2
Order By: Relevance
“…The upregulation of eNOS with flow in RAEC-only collagen gels is consistent with the animal studies showing upregulation of eNOS expression by shear stress. 29 No change in thrombomodulin and prostaglandin synthase is at variance with some previous reports, which suggest an upregulation of thromobomodulin 30 and prostacyclin 31,32 by shear stress. However, the magnitude of shear in the gels may not have been sufficient to generate changes in expression of these latter molecules.…”
Section: Protein Analysismentioning
confidence: 58%
“…The upregulation of eNOS with flow in RAEC-only collagen gels is consistent with the animal studies showing upregulation of eNOS expression by shear stress. 29 No change in thrombomodulin and prostaglandin synthase is at variance with some previous reports, which suggest an upregulation of thromobomodulin 30 and prostacyclin 31,32 by shear stress. However, the magnitude of shear in the gels may not have been sufficient to generate changes in expression of these latter molecules.…”
Section: Protein Analysismentioning
confidence: 58%
“…During exercise, blood flow increases to provide muscle with an adequate supply of oxygen and nutrients. It is well documented that flow/shear stress is an important signal regulating eNOS expression in blood vessels (19,27). Consequently, age-associated reductions in physical activity and associated increases in blood flow may remove an important signal for the maintenance of eNOS expression.…”
Section: Discussionmentioning
confidence: 99%
“…In the endothelium, it has been shown that NOS expression is regulated by flowmediated shear stress and is downregulated at sites with low flow. [12][13][14][15] Because AF leads to a loss of organized atrial contraction and to turbulent blood flow in the left atrium, we hypothesized that AF may cause a downregulation of NOS gene expression and function in the left atrial endocardium. The subsequent decrease in NO · concentration may lead to increased expression of PAI-1 and platelet aggregation and ultimately contribute to thrombosis in the left atrium.…”
Section: See P 2764mentioning
confidence: 99%